(untitled) (IJOVTECH, 2026)
Exams are a standard component of the educational system in every society across the globe. On the other hand, there has been a growing pattern of unethical behavior during examinations, which has harmed the evaluation of students in academic institutions. Earlier studies have shed light on the patterns and correlations of exam cheating in the educational sector. However, there is a paucity of information regarding the influence of the emotional state in relation to writing on exam cheating. The current paper examined the correlation between writing apprehension and examination malpractice. One hundred and eighty-seven (n=187) undergraduates enrolled in a public higher institution in Ebonyi State participated in the study. The respondents completed self-report measures of the Second Language Writing Anxiety Inventory (SLWAI) and Academic Dishonesty Scale. The study adopted a correlational research model for data analysis. The result demonstrated a significant positive correlation between writing anxiety and examination malpractice in undergraduates, r (185) = .31, p < .001, with writing concern contributing about 21% of the variation in examination malpractice. The study concludes that graphobia significantly determines cheating in higher education.